Gut microbiota influences colorectal cancer through immune cell interactions: a Mendelian randomization study - Linyi Zheng; Yuqiang Li; Cenap Güngör; Heming Ge (Discover Oncology)
Abstract Background Colorectal cancer (CRC) is the most prevalent malignant tumor of the digestive system globally, posing a significant threat to human health and quality of life. Recent studies have established associations between gut microbiota and immune cells with CRC; however, the mechanisms by which gut microbiota influence the development and progression of CRC through immune mediators remain poorly understood. Methods We conducted a two-sample, bidirectional Mendelian randomization analysis. We utilized 731 immune cell types and 473 gut microbial species along with colorectal cancer statistics from published summary statistics from genome-wide association studies (GWAS).The analysis employed several methodologies, including inverse variance-weighted (IVW) analysis, MR-Egger regression, the weighted median method, and both weighted and simple model approaches.Sensitivity analyses were performed to confirm the reliability of the Mendelian randomization results, and reverse Mendelian randomization was used to assess the overall impact of CRC on gut microbiota and immune cells. Results Our findings suggest a causal relationship involving nine immunophenotypes and five specific gut microbial taxa with CRC. Notably, the gut microbes Alloprevotella and Holdemania, along with immune cell types CD3 on CD28- CD8br and CD4 + T cells, demonstrated significant causal associations with CRC. Mediation analysis revealed that the association between Alloprevotella and CRC was mediated by CD4 + T cells, with a mediation effect of 6.48%. Additionally, Holdemania was found to mediate its association with CRC through CD3 on CD28- CD8br, exhibiting a mediation effect of 9.29%. Reverse Mendelian randomization did not indicate any causal effect of CRC on specific immune cells or gut microbiota. Two-sided sensitivity analyses revealed no evidence of heterogeneity or horizontal pleiotropy in our findings. Conclusions This comprehensive Mendelian randomization study enhances our understanding of the mechanisms by which gut microbiota affects CRC through immune cell interactions. Further investigations are warranted to unravel the underlying mechanisms linking gut microbiota, immune cells, and colorectal cancer.